2023
DOI: 10.1088/1741-2552/acc54e
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity pulsed ultrasound increases neurotrophic factors secretion and suppresses inflammation in in vitro models of peripheral neuropathies

Abstract: Objective: In this study, we aimed to verify the beneficial effects of low-intensity pulsed ultrasound (LIPUS) stimulation on two cell types: H2O2-treated RSC96 Schwann cells and THP-1 macrophages, used to model neuropathic inflammation. 
Approach: Using a set-up guaranteeing a fine control of the ultrasound dose at the target, different frequencies (38 kHz, 1 MHz, 5 MHz) and different intensities (20, 100, 500 mW/cm2) were screened to find the most effective experimental conditions for triggering bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…All the effects mentioned above are extremely important during the remobilization period, as immobilization leads to a decrease in protein synthesis and an increase in protein degradation, with consequent muscle atrophy (1,41), meaning that the anabolic stimulus of ultrasound is favorable to the trophic recovery of muscle tissue. Furthermore, since immobilization generates pro-inflammatory tissue characteristics, a reduction in angiogenic stimulus, as well as the replacement of contractile tissue by fibrous and fatty tissue (2,3,41), ultrasound may have an important action against these characteristics (37,42). Also to be taken into account is the nociceptive alteration that immobilization generates (4), which in turn can affect the dorsal root reflex and the axonal reflex, promoters of neurogenic inflammation (43,44), or be precisely caused by them.…”
Section: Discussionmentioning
confidence: 99%
“…All the effects mentioned above are extremely important during the remobilization period, as immobilization leads to a decrease in protein synthesis and an increase in protein degradation, with consequent muscle atrophy (1,41), meaning that the anabolic stimulus of ultrasound is favorable to the trophic recovery of muscle tissue. Furthermore, since immobilization generates pro-inflammatory tissue characteristics, a reduction in angiogenic stimulus, as well as the replacement of contractile tissue by fibrous and fatty tissue (2,3,41), ultrasound may have an important action against these characteristics (37,42). Also to be taken into account is the nociceptive alteration that immobilization generates (4), which in turn can affect the dorsal root reflex and the axonal reflex, promoters of neurogenic inflammation (43,44), or be precisely caused by them.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in vitro , Zhang et al (2019) reported an increased expression of anti-inflammatory-related genes such as arginase 1 (Arg1), peroxisome proliferator activated receptor gamma (PPAR-γ) and IL-4 involved in tissue regeneration, following 1.5 MHz ultrasound treatment of bone marrow-derived macrophages and raw264.7 cells, a murine derived macrophage-like cell line. Similarly, following ultrasound stimulation, human monocytic THP-1 macrophage-like cells treated with lipopolysaccharide (LPS) had decreased gene expression of pro-inflammatory of TNF-α and IL-8, and increased gene expression of IL-10 which promotes the resolution of inflammation, indicating that ultrasound can modulate cytokine expression in macrophages in vitro ( Fontana et al, 2023 ). LPS-stimulated macrophage-like cells, obtained from U937 monocyte-like cells, treated with 38 kHz ultrasound at 250 mW/cm 2 have been shown to significantly reduce the expression of pro-inflammatory cytokines in vitro ( Iacoponi et al, 2023 ).…”
Section: Effect Of Fus and Fus + Microbubbles: The Immune Hypothesismentioning
confidence: 99%
“…LIPUS affected the proliferation and myelinating activity of Schwann cells, in a both time-and duty ratio-dependent manner. Thus, LIPUS can be used to repair peripheral nerve injury and peripheral neuropathies [126,127]. The current knowledge about the influence of LIPUS on animal and human models revealed that LIPUS may have an impact on nerve regeneration and axonal alterations in the situation of carpal tunnel syndrome, transected nerve, dementia, and neurogenic erectile dysfunction [128,129].…”
Section: Nerve Repairmentioning
confidence: 99%